Optimal feeder service plan design of cargo express train in railway hub. (2nd July 2016) - Yin, Weichuan; He, Shiwei; Li, Haodong; He, Bisheng
Abstract: The feeder service plan (FSP) of cargo express train aims to utilize the train resources in railway hub in a more cost-effective way. So far in China, the feeder service operating mode with hump yard (FSOMH) in railway hub cannot meet freight transport demand, because of their low level of service. To improve the level of service of cargo express trains, a new feeder service operating mode with hump yard and railway logistics centre (FSOMHR) is proposed in this paper. A mixed integer programming model is also presented, which is based on a service network in railway hub. This model aims to minimize the cost of the cargo express train organization and number of local trains. In addition, the service time constraint and capacity constraint of service arcs are considered. The case study based on Hangzhou railway hub shows that the proposed solution method yields a better FSP. Under the FSOMHR, the departure volume of railcars increases by 58.70%, compared to FSOMH.